Simulation of different rules in stochastic flowshops - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
We consider a two-machine flowshop scheduling problem where machines are subject to random breakdowns. We define the stochastic machine dominance problem and suggest five rules for finding the makespan. We use simulation to find the performance of these five rules. Out of these five rules, one rule seems to perform well when machine 1 stochastically dominates machine 2, whereas when machine 2 stochastically dominates machine 1 another rule is found to be good. The results of the experimentation reveal that when uptimes and downtimes follow exponential distributions. Talwar rule performs well. The results of the experimentation also reveal that Johnson rule's performance is not that bad when machines break down.
Keywords: flowshop; breakdowns; simulation; makespan; RANDOM BREAKDOWNS; 2-MACHINE